The Rlm13 Gene, a New Player of Brassica napus–Leptosphaeria maculans Interaction Maps on Chromosome C03 in Canola - Raman, Harsh; Raman, Rosy; Qiu, Yu; Zhang, Yuanyuan; Batley, Jacqueline; Liu, Shengyi (Frontiers in Plant Science, 2021)
Canola exhibits extensive genetic variation for resistance to blackleg disease, caused by the fungal pathogen, Leptosphaeria maculans. Despite the identification of several Avr effectors and R (race-specific) genes, specific interactions between Avr-R genes are not yet fully understood in the Brassica napus- Leptosphaeria maculans pathosystem. In this study, we investigated the genetic basis of resistance in an F2:3 population derived from Australian canola varieties CB-Telfer (Rlm4)/ATR-Cobbler (Rlm4) using a single spore isolate of L. maculans, PHW1223. A genetic linkage map of the CB-Telfer/ATR-Cobbler population was constructed using 7,932 genotyping-by-sequencing based DArTseq markers, and subsequently utilised for linkage and haplotype analyses. Genetic linkage between DArTseq markers and resistance to PHW1223 isolate was also validated using the B. napus 60K Illumina Infinium array. Our results revealed that a major locus for resistance, designated as Rlm13, maps on chromosome C03. To date, no R gene for resistance to blackleg has been reported on the C subgenome in B. napus. Twenty-four candidate R genes were predicted to reside within the QTL region. We further resequenced both the parental lines of mapping population (CB-Telfer and ATR-Cobbler, > 80× coverage) and identified several structural sequence variants in the form of SNPs, InDels, and PAVs near Rlm13. Comparative mapping revealed that Rlm13 is located within the homoeologous A03/C03 region in ancestral karyotype block ‘R’ of Brassicaceae. Our results provide a ‘target’ for further understanding Avr-Rlm13 gene interaction as well as a valuable tool for increasing resistance to blackleg in canola germplasm.